TCF Bleaching of Eucalyptus tereticornis Kraft Pulps by MILOX Process - Bhatnagar, Anju (Indian Forester, 2023)
Conventional bleaching of kraft pulps needs chlorine or chlorine chemicals to obtain full brightness. Peroxy compounds are effective delignification agents and can use in chemical pulp bleaching. According to the literature, peroxy acids are reactive and selective in reaction with lignin. The residual lignin reactivity towards hydrogen peroxide (P) bleaching was significantly increased by the pretreatment of peroxy acid. The three different bleaching sequences such as (PFA)P, (PFA)PP, and (PFA)PAP were developed for the bleaching of unbleached kraft pulp. The sequences are based on pretreatment using peroxy formic acid (PFA) that makes the residual lignin of pulp more susceptible to attack by hydrogen peroxide. Sequential bleaching with peroxy formic acid followed by alkaline peroxide alone in one or two stages or separately by acid treatment produced bleached pulp with 82.42; 85.30 % ISO brightness and good properties. The strength properties of bleached pulp are tested and compared with the CEHH sequence in conventional bleaching and oxygen pre-bleaching, OCEH sequence. The results obtained from the bleached pulp by the MILOX method are similar to CEHH and OCEH bleaching sequences. The results are thoroughly discussed in the study.